2015
DOI: 10.1186/s40494-015-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Damage function for historic paper. Part I: Fitness for use

Abstract: Background:In heritage science literature and in preventive conservation practice, damage functions are used to model material behaviour and specifically damage (unacceptable change), as a result of the presence of a stressor over time. For such functions to be of use in the context of collection management, it is important to define a range of parameters, such as who the stakeholders are (e.g. the public, curators, researchers), the mode of use (e.g. display, storage, manual handling), the long-term planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 13 publications
0
43
0
Order By: Relevance
“…In such cases, degradation becomes unacceptable, objects are considered unfit for use and thus damaged. However, we have also shown that the level of acceptance of degradation depends on the value of the object [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In such cases, degradation becomes unacceptable, objects are considered unfit for use and thus damaged. However, we have also shown that the level of acceptance of degradation depends on the value of the object [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the contribution of 10 ppb NO 2 to the rate of DP loss was comparable to that of ~4 °C for some papers (acidic and rag). NO 2 also contributed to significant yellowing of some types of paper; however, as we have shown this is not seen as an important element of fitness by general library and archival readers and visitors [1]. The contribution of O 3 would still need to be studied quantitatively, although its concentration is usually lower than that of NO 2 in archival and library repositories [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose-response functions illustrate this approach. They enable the prioritization of the agents of deterioration and the definition of damage thresholds [2,10,11]. An example of an algorithm based on such mathematical functions is the preservation metrics developed by the Image Permanence Institute [12].…”
Section: Introductionmentioning
confidence: 99%